Mediation of Socioenvironmental Conflict in Macrodrainage Works: The Experience of the Municipal Government of Guarujá, São Paulo State, Brazil - Teixeira, Aniria Jose da Fonseca; Ribeiro, Andreza Portella; Silva, Leonardo Ferreira da (National Journal of City Management, 2024)
Urban growth has been correlated with substantial changes in land use, triggering socio-environmental conflicts. In Brazil, the lack of a tradition in mediating socio-environmental conflicts is evident through numerous lawsuits that often take years to reach a resolution. This study emphasized the actions taken by the Municipal Government of Guarujá (PMG) in 2022 as a tool for resolving socio-environmental conflicts without resorting to litigation. The research focused on the specific case of a macro-drainage project in the Santo Antônio neighborhood, which involved the relocation of 29 families from their homes with equivalent compensation guided by a Terms of Conduct Adjustment (TAC). This qualitative study was grounded in document analysis, a systematic literature review, and interviews with stakeholders. The study aimed to analyze how mediation techniques could contribute to resolving socio-environmental conflicts between public infrastructure projects and the local population. The research findings indicated that the PMG's initiatives were essential in creating a mediation space where, through dialogue, officials involved in the relocation process addressed the families' concerns, even amending clauses within the Comparative Data Market Method for Urban Areas, used for compensation payments, in accordance with legal instruments. This initiative led all the families involved to adhere to the negotiated terms, avoiding litigation and facilitating the project's realization.